2024
DOI: 10.1039/d3py01255g
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hydrogen bonding interaction energy on the polymerization kinetics of polymerizable deep eutectic solvent monomers

Liang Lin,
Ren'ai Li,
Guangxue Chen
et al.

Abstract: The fabrication of functional materials through the polymerization of polymerizable deep eutectic solvent monomers (PDES monomers) has emerged as a novel research field in recent years. Besides, in comparison to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…In a recent study, Lin et al investigated the effect of a PDES (consisting of quaternary ammonium salts as the HBAs and AA as the HBD) on the polymerization kinetics of the monomer component (AA) compared to the utilization of the inert solvents DMF, DMSO, and methanol. 35 The authors reported a significantly high CC conversion (∼99%) in PDES medium as opposed to with traditional solvents (less than 30% conversion), besides the high rate of conversion. The main reason for this was attributed to the increased CC bond activity of the AA monomer (which acted as the HBD) resulting from the hydrogen bonding with the quaternary ammonium salt-based HBAs.…”
Section: Dess For Green Polymer Synthesismentioning
confidence: 94%
“…In a recent study, Lin et al investigated the effect of a PDES (consisting of quaternary ammonium salts as the HBAs and AA as the HBD) on the polymerization kinetics of the monomer component (AA) compared to the utilization of the inert solvents DMF, DMSO, and methanol. 35 The authors reported a significantly high CC conversion (∼99%) in PDES medium as opposed to with traditional solvents (less than 30% conversion), besides the high rate of conversion. The main reason for this was attributed to the increased CC bond activity of the AA monomer (which acted as the HBD) resulting from the hydrogen bonding with the quaternary ammonium salt-based HBAs.…”
Section: Dess For Green Polymer Synthesismentioning
confidence: 94%
“…56,57 More recent advances by Li et al have unveiled the impact of hydrogen bonding interaction energy on the polymerization kinetics of these systems, exploring an array of quaternary ammonium salt homologs and AA. 58…”
Section: Polymerizable Deep Eutectic Solvents (Pdess): Types and Prop...mentioning
confidence: 99%
“…Despite having been the subject of extensive studies for more than a century, hydrogen bonding interactions are still at the heart of numerous investigations within the scientific community (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). This is because they play a crucial role in various fields, from molecular recognition processes to condensed matter via the self-assembling of macromolecules (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%